Rancang Bangun Sistem Kendali Sepeda Listrik Berbasis Arduino - Suhendro, Budi; Joni; Harsono, Djiwo (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
A bicycle control system has been made using the PWM principle to adjust the motor speed byusing a distance sensor as a safety system on the highway. The background of this research,electric bicycles have still not installed a safety system that directly connects motor speed usingthe principle of Pulse Width Modulation (PWM). The control system that is designed are addedan ultrasonic sensor on the front of the bicycle that serves to measure the distance of the rider'sbicycle with other vehicles. Variation of the specified distance is equal to ? 1 meter, ? 2 meters,? 3 meters, and > 3 meters, so the risk of accidents on the highway can be decreases. Thepurpose of this research is design and build a control system using the PWM principle toregulate the rotation speed of the motor and safety systems on electric bicycles. The results ofthis research are in barrier-free condition, electric bicycles can drove with average maximumspeed of 28 km/hour. The speed of an electric bicycle that is affected by the front ultrasonicsensor at a high speed at a distance of 3 meter, 2 meter and 1 meter, respectively; 20.6km/hour; 15.5 km/hour; and 5 km/hour. The right ultrasonic sensor has succeed to activatingthe buzzer at a distance of ? 100 cm.